Can laser treatment improve quality of life of hirsute women? - Alizadeh N; Ayyoubi S; Naghipour M; Hassanzadeh R; Mohtasham-Amiri Z; Zaresharifi S; Gharaei Nejad K (Dove Medical Press, 2017)
Narges Alizadeh,1 Sharad Ayyoubi,2 Mohammadreza Naghipour,3 Rasool Hassanzadeh,2 Zahra Mohtasham-Amiri,3 Shirin Zaresharifi,4 Kaveh Gharaei Nejad1 1Dermatology Department, School of Medicine, Guilan University of Medical Sciences, 2General Practice, School of Medicine, Guilan University of Medical Sciences, 3Community Medicine Department, School of Medicine, Guilan University of Medical Sciences, Rasht, 4General Practitioner, School of Medicine, Tehran University of Medical Sciences, Tehran, Iran Background: Hirsutism can have negative impacts on psychosocial aspects of women’s lives and reduce their quality of life (QOL). The aim of this study was to assess the QOL of these women during laser treatment. Patients and methods: Eighty-eight women with unwanted facial hair underwent laser therapy. Each patient completed a questionnaire consisting of a modified Dermatology Life Quality Index (DLQI) and visual analog scale (VAS) before the first, third, and fifth sessions of laser therapy. Interval between the sessions was 4–6 weeks. Statistical analyses were done using SPSS software version18. Results: The DLQI scores before treatment, and at third and fifth sessions were 7.75±2.36, 5.55±1.88, and 4.14±0.64, respectively (P<0.0001). Also, VAS scores had a decreasing trend between the first and second treatment sessions as the mean patient VAS score fell from 10±0.04 to 5.53±2.41 (P<0.0001). The DLQI scores were significantly different according to areas of hair growth and number of involved areas. There were no significant differences with regard to response to treatment and mean of DLQI score according to the level of education, marital status, and employment status. Conclusion: Hair removal with laser therapy can improve the QOL in hirsute women. Also, socioeconomic status does not affect the satisfaction rate of laser therapy for hair removal. Keywords: hirsutism, laser, quality of life, satisfaction, psychosocial